Magnetoelastic sensors based on soft amorphous magnetic alloys - Barandiaran, J.M.; Gutierrez, J. (Sensors and actuators. A. Physical., 1997)
Magnetoelastic properties of soft amorphous magnetostrictive alloys are used in high efficiency sensors: when negative magnetostriction (Co-rich) samples are used, a stress sensor can be easily constructed by using the continuous and linear increase of the magnetoelastic anisotropy induced by the applied stress. In this work we report on one of these sensors with a figure of merit of 104 and a range of utilization that extends almost to the theoretical elastic limit of the sample. On the other hand, high positive magnetostriction (Fe-rich) metallic glasses are characterized by the frequency of the longitudinal vibrational mode of the samples, ωr being a function of the applied static field H. Studies performed about the performance of ωr as a carrier of information (i.e., object recognizer) are discussed, and a new sample configuration for this purpose is presented.